Matematyka

Autorzy:Małgorzata Dobrowolska, Marcin Karpiński, Marta Jucewicz

Wydawnictwo:GWO

Rok wydania:2016

Wpisz odpowiednie wyrażenia. 4.6 gwiazdek na podstawie 5 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

a)

`(....)^2=4x^2`

`4x^2=2^2*x^2=(ul(2x))^2`

 

`(....)^2=0,04x^2y^4`

`0,04x^2y^4=0,2^2*x^2*(y^2)^2=(ul(0,2xy^2))^2`

 

`(....)^2=9/16a^4`

`9/16a^4=(3/4)^2*(a^2)^2=(ul(3/4a^2))^2`

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))`

b)

`(...)^3=27a^3b^9`

`27a^3b^9=3^3*a^3*(b^3)^3=(ul(3ab^3))^3`

 

`(...)^3=-1/8a^6`

`-1/8a^6=(-1/2)^3*(a^2)^3=(ul(-1/2a^2))^3`

 

`(...)^3=1/64x^3`

`1/64x^3=(1/4)^3*x^3=(ul(1/4x))^3`

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))`

c)

`(...)^2=(a^2)/(4b^4)`

`(a^2)/(4b^4)=(a^2)/(2^2*(b^2)^2)=(a^2)/((2b^2)^2)=(ul(a/(2b^2)))^2`

 

`(...)^3=(-8z^9)/(0,001x^3)`

`(-8z^9)/(0,001x^3)=((-2)^3*(z^3)^3)/(0,1^3*x^3)=((-2z^3)^3)/((0,1x)^3)=(ul((-2z^3)/(0,1x)))^3`

 

`(...)^3=(x^6y^9z^12)/(8a^15)`

`(x^6y^9z^12)/(8a^15)=((x^2)^3*(y^3)^3*(z^4)^3)/(2^3*(a^5)^3)=((x^2y^3z^4)^3)/((2a^5)^3)=(ul((x^2y^3z^4)/(2a^5)))^3`